Financial Feasibility Analysis of Crystal Guava Cultivation in Bantarsari Village, Bogor - Wilistanti, Mareta Gangsar; Gandhy, Abel; Syafaat, Fitra (Institute of Computer Science (IOCS), 2025)
Bantarsari Village, Rancabungur Sub-district, Bogor Regency, is known as the National Crystal Guava Village. However, as long as this business has been running, there has never been an analysis of financial feasibility. For this reason, this study was made with the aim of analyzing the financial feasibility of crystal guava cultivation in Bantarsari Village based on indicators of NPV, IRR, Net B/C, PP and sensitivity analysis to a 5% decrease in price and 10% decrease in production. The results showed that this cultivation is financially feasible with an NPV value of IDR. 187,308,181, IRR of 20%, Net B/C of 1.41, and PP for 3 years and 7 months; even in the scenario of a 5% decrease in selling prices and 10% production, the business remains feasible. Therefore, based on the results of this study, it is known that the crystal guava cultivation business in Bantarsari Village is financially feasible to run because it is financially profitable, and has the resilience to business risks such as a decrease in selling prices and a decrease in production